Compartmentalized 3D Tissue Culture Arrays under Controlled Microfluidic Delivery - Burcu Gumuscu; Hugo J. Albers; Albert van den Berg; Jan C. T. Eijkel; Andries D. van der Meer (Scientific Reports, 2017)
Abstract We demonstrate an in vitro microfluidic cell culture platform that consists of periodic 3D hydrogel compartments with controllable shapes. The microchip is composed of approximately 500 discontinuous collagen gel compartments locally patterned in between PDMS pillars, separated by microfluidic channels. The typical volume of each compartment is 7.5 nanoliters. The compartmentalized design of the microchip and continuous fluid delivery enable long-term culturing of Caco-2 human intestine cells. We found that the cells started to spontaneously grow into 3D folds on day 3 of the culture. On day 8, Caco-2 cells were co-cultured for 36 hours under microfluidic perfusion with intestinal bacteria (E. coli) which did not overgrow in the system, and adhered to the Caco-2 cells without affecting cell viability. Continuous perfusion enabled the preliminary evaluation of drug effects by treating the co-culture of Caco-2 and E. coli with 34 µg ml−1 chloramphenicol during 36 hours, resulting in the death of the bacteria. Caco-2 cells were also cultured in different compartment geometries with large and small hydrogel interfaces, leading to differences in proliferation and cell spreading profile of Caco-2 cells. The presented approach of compartmentalized cell culture with facile microfluidic control can substantially increase the throughput of in vitro drug screening in the future.